2019
DOI: 10.1002/jbm.b.34506
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized liver matrix as substrates for rescue of acute hepatocytes toxicity

Abstract: More and more scholars regard the lesion of liver cirrhosis as a series of progressive clinical stages. Besides, liver cirrhosis is a late stage of scarring (fibrosis) of the liver, and has long been a common cause of death for the global adult population, thus, the treatment of liver cirrhosis is a key point investigated in the biomedical field. Here, we propose a novel hypothesis; if decellularized liver matrix (DLM) is possible injected into the injurant‐induced fiberized liver via the hepatic portal vein t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Several studies have used the DCL ECM in a solubilized form to generate 3D injectable hydrogels. 7,11 The viability and functionality of hepatocytes have been shown to be significantly improved in DCL hydrogels compared to those observed in collagen hydrogels. 39 Recent studies have also reported 3D bioprinting of liver cells, in which bioprinted hepatocytes and nonparenchymal cells in 3D architecture have been reported to be metabolically and functionally active.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have used the DCL ECM in a solubilized form to generate 3D injectable hydrogels. 7,11 The viability and functionality of hepatocytes have been shown to be significantly improved in DCL hydrogels compared to those observed in collagen hydrogels. 39 Recent studies have also reported 3D bioprinting of liver cells, in which bioprinted hepatocytes and nonparenchymal cells in 3D architecture have been reported to be metabolically and functionally active.…”
Section: Discussionmentioning
confidence: 99%
“…For example, decellularized liver (DCL) tissue and hydrogels based on DCL extracellular matrix (ECM) have been used extensively for liver tissue engineering, where all of the cellular and immunogenic components of ECM proteins are removed only to retain the native ECM. 7 Recently, a few studies have reported three-dimensional (3D) cultures of hepatocytes along with other liver cells, including endothelial and stellate cells, to form a functional liver construct. 8−10 Minami et al developed a 3D liver tissue equivalent using human-induced pluripotent stem cells and rat DCL-based scaffolds that expressed albumin (ALB) and cytochrome P450 3A4 (CYP3A4) genes after 48 h of recellularization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop a completely competent transplantable organ utilizing BEL, the two stages of decellularization and recellularization are necessary ( Badylak et al, 2011 ; Baptista et al, 2011 ). Decellularization seeks to create a biocompatible decellularized scaffold that preserves the three-dimensional architecture and biochemical content of the original tissue while removing the cellular material to decrease the immunological reactivity ( Uygun et al, 2010 ; Debnath et al, 2020 ; Hou et al, 2020 ; Moulisova et al, 2020 ). Enzymes and chemicals, along with mechanical agitation, freezing/thawing, and sonication, are various strategies for decellularization by disturbing cells and liberating their substance.…”
Section: Principals For Bioengineered Liversmentioning
confidence: 99%
“…Recent reports document that decellularized liver scaffolds promote liver regeneration after partial hepatectomy 95 and rescue of acute hepatocyte toxicity. 96 Decellularized liver matrix-modified scaffolds have been shown as a substrate for hepatocyte culture 97 as well as potential hepatocyte carriers in BAL support systems and implantable liver constructs. 98 These studies provide further proof that this technology may one day deliver viable constructs for drug discovery and toxicology applications, as well as for transplantation.…”
Section: Recellularized Livermentioning
confidence: 99%